2004
DOI: 10.1016/j.amjhyper.2003.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Aortic pulse pressure is related to the presence and extent of coronary artery disease in men undergoing diagnostic coronary angiography: a multicenter study

Abstract: In this multicenter study, aortic PP was significantly correlated with the presence and extent of CAD in patients without antihypertensive therapy. This correlation, however, was independent of other risk factors for CAD in men but not in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 22 publications
2
44
0
3
Order By: Relevance
“…In subjects with preserved EF, it has been shown that the level of PP is proportional to the number of atherosclerotic coronary stenosis. 13 On the opposite, arterial occlusion that represents the major consequences of coronary stenosis is obviously associated to the extent of myocardial infarction and necrosis, and hence to reduced aortic PP (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In subjects with preserved EF, it has been shown that the level of PP is proportional to the number of atherosclerotic coronary stenosis. 13 On the opposite, arterial occlusion that represents the major consequences of coronary stenosis is obviously associated to the extent of myocardial infarction and necrosis, and hence to reduced aortic PP (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…11,16,17 Invasive intra-aortic SBP and DBP were measured at the time of coronary angiography using a fluid-filled catheter at baseline before any injection of contrast medium as previously documented. 13 Aortic PP was calculated as the difference between aortic SBP and aortic DBP. Heart rate was recorded using electrocardiographic monitoring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Furthermore, findings of the multicentre ESCAPP study showed that aortic PP was significantly related to the presence and extent of coronary artery disease in patients without antihypertensive therapy. 23 It is surprising that in various mega trials addressing the performance of various treatment modalities for hypertension, their influence on PP is not taken into account. Currently, the choice of the drug for the initial treatment of hypertension is very strongly debuted.…”
Section: Discussionmentioning
confidence: 99%